Night shifts and consumption of energy drinks by healthcare personnel - Alberto Farinetti; Francesca Coppi; Beatrice Salvioli; Anna Vittoria Mattioli (Beverage Plant Research)
The consumption of drinks with a high caffeine content is a growing phenomenon not only among young people but also among individuals who work night shifts, including healthcare workers. In young people, the motivations that lead to taking energy drinks are linked to performance in studies and recreational activities. In healthcare workers, the motivations are linked to work performance and the need to maintain a high level of wakefulness during the night. This review analyzes the studies published on the consumption of energy drinks in healthcare personnel and the changes that have occurred in recent years also following the stress caused by the recent pandemic on healthcare.